1976
DOI: 10.1073/pnas.73.6.2147
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of protoplasts of Bacillus megaterium.

Abstract: Protoplasts of two doubly auxotrophic strains of Bacillus megaterium were fused by nascent calcium phosphate or by polyethylene glycol treatment, and then allowed to revert to bacillary form on selection media. The colonies formed were analyzed and found to be mixed populations of individual bacteria apparently containing parental, recombinant, and segregating genotypes. The evidence suggested that segregation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

1978
1978
1996
1996

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(57 citation statements)
references
References 11 publications
2
55
0
Order By: Relevance
“…Artificially induced fusion has been demonstrated in a number of animal cells and plant and bacterial protoplasts (Harris & Watkins, 1965;Power et al, 1970;Fodor & Alfoldi, 1976). It was reasonable to expect that yeast protoplasts could also be fused without any difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Artificially induced fusion has been demonstrated in a number of animal cells and plant and bacterial protoplasts (Harris & Watkins, 1965;Power et al, 1970;Fodor & Alfoldi, 1976). It was reasonable to expect that yeast protoplasts could also be fused without any difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Their method, however, was modelled on a technique used for fusion of mammalian cells (Pontecorvo et a/., 1977) which employs a lower inolecular weight PEG (mol. wt 1540) for fusion, while the method described here is similar to the Bacillus system (Fodor & Alfoldi, 1976;Schaeffer et a/., 1976) which employs PEG 6000. With the method of Hopwood et al (1977), fused protoplasts were plated undiluted, and recombinant frequencies were determined after spore formation on confluent lawns of mycelial growth.…”
Section: Discussionmentioning
confidence: 99%
“…A lower but significant frequency of recombinants was achieved without PEG treatment. These were presumably induced to fuse by the Ca2+ ions present in medium P (Fodor & Alfoldi, 1976). Dilution of mixed protoplasts in distilled water before plating reduced the number of recombinants 100-fold.…”
Section: Genetic Recombination Induced By Protoplast Fusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fodor et al 16 ) reported that segregating genotypes appeared during the protoplast fusion of Bacillus megaterium. In our case, segregants did not appear after repeated transfer of the fusant from one slant to another.…”
Section: Discussionmentioning
confidence: 99%